Effect of enviromental factors at multiple landscape scales on bird community in riparian ecosystem at Mun-Chi River confluence, Thailand - Warut Chaleekarn; Prateep Duengkae; Chattraphas Pongcharoen; Nantida Sutummawong; Pisut Nakmuenwai; Sasithon Siripin; Chanon Chirachitmichai; Wuttisak Kummoo; Paanwaris Paansri; ‪Warong Suksavate (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Chaleekarn W, Duengkae P, Pongcharoen C, Sutummawong N, Nakmuenwai P, Siripin S, Chirachitmichi C, Kummoo W, Paansri P, Suksavate W. 2022. Effect of environmental factors at multiple landscape scales on bird community in riparian ecosystem at Mun-Chi River confluence, Thailand. Biodiversitas 23: 5194-5204. Wetland and riparian ecosystem is an important migratory stopover for land and water birds in the East Asian - Australasian Flyway. Understanding relationship patterns between bird communities and environmental factors at multi-spatial scales within a landscape context could contribute to the conservation and management of bird biodiversity in wetland ecosystems. The landscape metrics index is critical in revealing the relationship between the composition of bird communities and habitats at both local and landscape scales. This study aims to determine the effect of the environmental factors at different designated spatial scales on the composition of local bird communities in terms of species and feeding guilds. Our study conducted a bird survey using 227-point transects along 40 tracks across different land cover types surrounding the Mun-Chi River confluence. Canonical correspondence analysis (CCA) was used to quantify the association between bird communities, represented by species and feeding guilds, and environmental factors with the integration of multilevel habitat metrics. From the results, the CCA showed patterns of the community-environmental association at multiple scales of patch, class, and landscape characteristics with the proportional explanation of 54% and 61.82% for the composition of species and feeding guilds, respectively. The results indicated the premise that the majority of bird species respond to the habitat at the local scale. Large forest patches can maintain migratory and resident bird species. Moreover, most avian groups were arranged primarily in a large forest core area, forest area, and Shrubland PA. The results confirmed existing information on feeding guilds. The prediction map of the principal component of avian species composition was created from the association with the drivers of land use, including crops, perennial farmland, and water body on the edge of forests. Therefore, wetland management must be done at both local and landscape scales to preserve suitable avian habitats.